2007
DOI: 10.1111/j.1439-0531.2007.00852.x
|View full text |Cite
|
Sign up to set email alerts
|

Vulvar Discharge Syndrome in Loosely Housed Finnish Pigs: Prevalence and Evaluation of Vaginoscopy, Bacteriology and Cytology

Abstract: A total of 21 sow herds were randomly chosen to determine the prevalence of vulvar discharge syndrome (VDS) in loosely housed sows. The median VDS prevalence was low as expected, 0% (range 0-4.5%). Nine of the 655 animals examined (1.4%, 95% CI 0.5-2.3) displayed signs of VDS in 21 non-problem herds. In addition, five VDS problem farms were visited to gather more animals affected with the syndrome in order to estimate which methods of examination are useful. Altogether, 19 VDS animals and 19 healthy controls w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
0
4
0
6
Order By: Relevance
“…The presence of pathogenic strains of E coli and several other bacteria including C perfringens in the vulval discharges of sows has been previously reported by Oravainen and others (2008). Other studies have also demonstrated that the incidence of health problems in sows was a risk factor for the occurrence of diarrhoea in suckling piglets (Dewey and others 1995, Wittum and others 1995).…”
Section: Discussionmentioning
confidence: 57%
“…The presence of pathogenic strains of E coli and several other bacteria including C perfringens in the vulval discharges of sows has been previously reported by Oravainen and others (2008). Other studies have also demonstrated that the incidence of health problems in sows was a risk factor for the occurrence of diarrhoea in suckling piglets (Dewey and others 1995, Wittum and others 1995).…”
Section: Discussionmentioning
confidence: 57%
“…and Streptococcus spp. are isolated from the urogenital tract in case of cystitis, endometritis, and mastitis [34,35]. Considering that these are unspecific bacteria originating from feces and environment, it is important to keep hygiene before and during parturition at a high level [36].…”
Section: Management and Hygienementioning
confidence: 99%
“…Vaginaler Ausfluss wird genauso beobachtet wie umrauschende Sauen, die gynäkologisch unauffällig sind. Bisher wurden Endometritiden beim Schwein klinisch schlicht als differenzialdiagnostische Komponente dem so genannten "vulval/vulvar discharge syndrome" untergeordnet (60,65,66 Während die klinische Nomenklatur fehlt, ist die pathomorphologische "nur" uneinheitlich. Es versteht sich von selbst, dass auch dahingehend eine Vereinheitlichung notwendig ist, da die klinischen Endometritisformen pathomorphologisch beschrieben werden müssen und die pathomorphologische Untersuchung, anders als beim Rind, beim Schwein im Rahmen der Abklärung von Fruchtbarkeitsproblemen eine herausragende Rolle spielt (4,60).…”
Section: Nichtpuerperale Uterusentzündungen Nomenklaturunclassified
“…Ein nicht unerheblicher und gelegentlich eben fataler Eintrag erfolgt während der Brunst durch den natürlichen Deckakt oder die Besamung (8). Wie ähnlich auch für die puerperale Uterusentzündung beschrieben, stammen die Bakterien aus Vagina und/oder Harnblase (60,78) oder werden als klassische Kontaminanten aus der Umgebung (Fäkalien, Gerätschaften) eingetragen (11,66). Nicht zu unterschätzen ist der Eber, dessen Diverticulum praeputiale eine Vielzahl unterschiedlichster Bakterien beherbergt (6,60).…”
Section: äTiologie Und Pathogeneseunclassified
See 1 more Smart Citation